Revisiting Robert Reiner to think about current police culture. Some tensions in a community policing experience - Ghiberto, Luciana (Universidad Nacional del Litoral, 2020)
The present article aims to describe with detail some cultural features of the community policing experience in Santa Fe province using as a prism of analysis the work that Robert Reiner has done on police culture, an unavoidable author in the social studies of the police. It aims to shed light on particular characteristics of this police segment and discover continuities with the traditional police, placing itself at the core of theoretical developments on police culture. It is based on document analysis and on qualitative analysis of 53 semi-structured interviews conducted with community police officers in the city of Santa Fe between 2015 and 2018.